Ultra-Wideband, Short Pulse Electromagnetics 9 - Sabath, Frank.; Sabath, Frank.; Giri, D.V.; Giri, D.V.; Rachidi, Farhad.; Rachidi, Farhad.; Kaelin, Armin.; Kaelin, Armin. (Springer New York : Imprint: Springer, 2010)
Ultra-wideband (UWB), short-pulse (SP) electromagnetics are now being used for an increasingly wide variety of applications, including collision avoidance radar, concealed object detection, and communications. Notable progress in UWB and SP technologies has been achieved by investigations of their theoretical bases and improvements in solid-state manufacturing, computers, and digitizers. UWB radar systems are also being used for mine clearing, oil pipeline inspections, archeology, geology, and electronic effects testing. Ultra-wideband Short-Pulse Electromagnetics 9 presents selected papers of deep technical content and high scientific quality from the UWB-SP9 Conference, which was held from July 21-25, 2008, in Lausanne, Switzerland. The wide-ranging coverage includes contributions on electromagnetic theory, time-domain computational techniques, modeling, antennas, pulsed-power, UWB interactions, radar systems, UWB communications, and broadband systems and components. This book serves as a state-of-the-art reference for scientists and engineers working in these applications areas.